INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AS A CATALYST FOR LIFELONG LEARNING AND PROFESSIONAL GROWTH - Nykyporets, Svitlana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
This article explores the role of Information and Communication Technology (ICT) as a catalyst in lifelong learning and professional development. By evaluating the integration and impact of ICT tools across various educational settings, the study highlights the enhanced learning outcomes, increased engagement, and improved accessibility these technologies offer. The research underscores the necessity of supportive policy frameworks and equitable access to maximize the benefits of ICT. Future research directions include examining long-term effects, integration of emerging technologies, and the development of inclusive learning environments. This study provides valuable insights for educators, policymakers, and industry leaders aiming to leverage ICT for continuous learning and professional growth.